2015
DOI: 10.5194/acp-15-13377-2015
|View full text |Cite
|
Sign up to set email alerts
|

Organic nitrate aerosol formation via NO<sub>3</sub> + biogenic volatile organic compounds in the southeastern United States

Abstract: <p><strong>Abstract.</strong> Gas- and aerosol-phase measurements of oxidants, biogenic volatile organic compounds (BVOCs) and organic nitrates made during the Southern Oxidant and Aerosol Study (SOAS campaign, Summer 2013) in central Alabama show that a nitrate radical (NO<sub>3</sub>) reaction with monoterpenes leads to significant secondary aerosol formation. Cumulative losses of NO<sub>3</sub> to terpenes are correlated with increase in gas- and aerosol-organic nit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
199
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(212 citation statements)
references
References 98 publications
12
199
1
Order By: Relevance
“…In areas with predominant monoterpene emissions, the background value is 3.1 ± 0.6 ‰ . Areas with a strong biomass burning and urban influence a background value of 1.7 ± 0.1 ‰ is reported, whereas ambient organic aerosol with a strong isoprene influence under low NO conditions shows an increased value of 6.5 ± 2.2 ‰ (Hu et al, 2015).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In areas with predominant monoterpene emissions, the background value is 3.1 ± 0.6 ‰ . Areas with a strong biomass burning and urban influence a background value of 1.7 ± 0.1 ‰ is reported, whereas ambient organic aerosol with a strong isoprene influence under low NO conditions shows an increased value of 6.5 ± 2.2 ‰ (Hu et al, 2015).…”
mentioning
confidence: 99%
“…Field measurements have shown that the major aerosol-phase product of monoterpene oxidation with nitrate radical is likely a hydroperoxy nitrate (C 10 H 17 NO 5 ) whereas the analogous isoprene oxidation product has a contribution of less than 1 % of the total organic nitrate and occurs more in gas phase (Ayres et al, 2015). Laboratory studies suggested that isoprene-derived 20 organic nitrates are formed from SOA reactions, but undergo substitution reactions in which nitrate is substituted by sulfate (Darer et al, 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations